Preliminary studies of a possible normal-conducting LINAC option for the UK's new light source - Walker, R; Bartolini, R; Christou, C; Han, J (2011)
We report on recent studies of an X-band linac as a potential driver for a soft X-ray FEL facility, including cost optimization and beam dynamics issues.